The Development of Learning Material Model in Writing Scientific Papers by Using Guided Inquiry Method at Universitas PGRI Sumatera Barat - Mana, Lira Hayu Afdetis (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
This research is motivated by the difficulties of students in determining the topic of scientific writing, difficulties in conveying ideas and limitations of references. This study aims to develop a learning model for writing scientific papers using the guided inquiry method. This type of research is development research. This study uses a 4-D development research design. The results of this study are as follows: (1) the material for writing scientific papers is difficult because students do not understand the concept of Scientific Writing. (2) in developing scientific work students do not yet know the systematics of scientific writing and students often make ineffective sentences (3) students really need freedom in determining writing topics and ideas (4) most students need the concept of learning to write scientific papers, (5) most students need lecturer guidance in their writing, (6) most students need systematic scientific work concepts, (7) most students need lots of references to write scientific papers. Based on the analysis of student needs, it is necessary to develop a Guided Inquiry-Based Scientific Writing Textbook that provides opportunities for students to find their own concept of learning to write scientific papers. Through Guided Inquiry, students are trained to think critically with teacher guidance.